1998
DOI: 10.2214/ajr.171.2.9694449
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of diagnostic imaging and subsequent autopsy findings in patients with pulmonary embolism.

Abstract: who underwent lung scintigraphy for suspected pulmonary embolism and for whom the pul monary embolism was proven at autopsy. MATERIALS AND METHODS. Weperformed a longitudinal follow-upstudyof 1210consecutive patients who underwent scintigraphic imaging for suspected pulmonary embo lism. Patients for whom pulmonary embolism was proven at autopsy within 30 days of lung scintigraphy were studied. Diagnostic testing and risk factors were compared in patients with and without an antemortem diagnosis of pulmonary em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 12 publications
2
22
0
1
Order By: Relevance
“…Using multidetector row systems, we have shown that 18% of patients have emboli in their subsegmental arteries as the most proximal location of PE. These findings compare well with the range of 6-36% of subsegmental PE reported in the literature [4][5][6]. Importantly, despite the expected superior imaging quality of MDCT, we did not detect a difference between the ability of MDCT and SDCT to localize PE.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…Using multidetector row systems, we have shown that 18% of patients have emboli in their subsegmental arteries as the most proximal location of PE. These findings compare well with the range of 6-36% of subsegmental PE reported in the literature [4][5][6]. Importantly, despite the expected superior imaging quality of MDCT, we did not detect a difference between the ability of MDCT and SDCT to localize PE.…”
supporting
confidence: 89%
“…However, among a number of laboratory methods, the platelet function analyzer-100 (PFA-100) has been used in several studies, some of which have shown that ASA resistance defined by results from the PFA-100 predict an increased risk of recurrent thrombosis [1][2][3][4]. In some papers, single determinations on the PFA-100 have been used because the coefficient of variance (CV) has been reported to be about 10% [5,6]. However, in a study establishing reference intervals in healthy men, we found a CV of about 13%, which increased considerably during ASA therapy (unpublished data).…”
Section: Disclosure Of Conflict Of Interestsmentioning
confidence: 99%
“…This is in contrast to fatal, in-hospital PE deaths for which not all clinical diagnoses of fatal PE are confirmed by autopsy. 10 Conversely, the percentage of clinically unsuspected PE causing sudden death has been reported to be as high as 50% 11 to 80%. 12 Here, we report the first autopsy-based study involving a large number (578) of consecutive out-of-hospital fatal PE cases in NYC.…”
Section: Editorial See P 2189 Clinical Perspective On P 2225mentioning
confidence: 99%
“…48,49 It is assumed that the presence of such emboli may indicate current DVT that potentially heralds more severe embolic events. 37,46,50 A burden of small peripheral emboli is also thought to have prognostic relevance in individuals with cardiopulmonary disease 46 and for the de- velopment of chronic pulmonary hypertension in patients with thromboembolic disease. 46 Although the accuracy of conventional single-slice spiral CT for the detection of isolated peripheral emboli may be limited, encouraging data are accumulating on the high negative predictive value of a normal spiral CT study 29,[51][52][53][54][55][56][57][58][59][60] (Table 2).…”
Section: Detection and Treatment Of Isolated Peripheral Pulmonary Embmentioning
confidence: 99%